The role of the pathologist in the oncology team - Soeripto, Soeripto (Universitas Gadjah Mada, 1990)
It is clear that the function of the pathologist is to determine the definite diagnosis. Many physicians think that the role of the pathologist is limited to the hospital. In the oncology team the pathologist has an important role not only in the hospital but also in the community.The role of the pathologist in the oncology team among others are in secondary prevention, for an early cancer detection program in the community; to help the team in improving the health services in the population; to prepare the population-based cancer registration; to determine the definite diagnosis, stage, managementof cancer patients in the hospital, and to evaluate therapeutic reaction and management result of cancer patients in the hospital.Key Words: role of pathologists - fine needle aspiration biopsy - frozen section - population-based cancer registry - stages of cancer